HOW MOBILE MEDIA ENABLED AND LIMITED ONLINE CIVIC PARTICIPATION AMONG LOW-INCOME U.S. YOUNG PEOPLE DURING THE PANDEMIC - Ramirez, Johnny; Jimenez, Carlos; Clark, Lynn Schofield (AoIR Selected Papers of Internet Research, 2021)
This paper presents comparative research from two youth-centered interdisciplinary ethnographic research projects in media studies, social work, and education. Originally designed as in-person interventions meant to provide digital media literacy and civic leadership development activities for 35 Latinx, Black, Indigenous, Asian American and White young people between ages 15-20 living in low-income neighborhoods, the experience of the COVID-19 pandemic forced both projects to take place online. Whereas each project found some benefits to holding endeavors in an online rather than an in-person environment, this paper centers on similar patterns that emerged across the projects in how and why differing participants dropped out over the one-year period between March 2020 through March 2021. The central research question of this paper is: what are the prospects for and barriers to online civic participation activities in the everyday lives of young people who, along with their families, are experiencing economic precarity and other forms of marginalization? The paper explores how mobile media were put to use for coping with everyday life during the pandemic, revealing some assumptions about both coping and online civic engagement that were dismantled.The analysis of these experiences force a reckoning with structural inequities that existed prior to the pandemic and that were further exacerbated because of it. The paper thus unearths new questions regarding how to design online civic participation activities involving young people with multiply intersecting experiences of both marginalization and resilience.